PENGARUH NON PERPFORMING LOAN (NPL) dan NET INTEREST MARGIN (NIM) TERHADAP RETURN ON ASSET (ROA) bank bjb Periode Tahun 2013-2017 - Nugraha, Heri; Iis, Komariah (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2018)
Financial performance has become one of the considerations about the condition of a bank. Many factors affect the financial performance of a bank. Therefore, this study examines the effect of Non Performing Loan (NPL) and Net Interest Margin (NIM) of the Return On Asset ( ROA) in bank bjb 2013-2017. Data analysis method used is multiple linear regression analysis which is previously performed classical assumption, such as normality test, multicollinearity test, autocorrelation test, and heteroskedastisitas test. Hypothesis testing by using the F test and t test. The Results from this study indicates that NPL significant negative effect on ROA. NIM significant positive effect on ROA. The amount of determination degree test (Adjusted R Square) is equal to 0.793, that means the independent variable such as NPL and NIM have the impact on ROA of 79,3% . Meanwhile, the remaining 20,7% is explained by other variables outside the model of this study .